2022
DOI: 10.3390/signals3020023
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on MIMO-OFDM Systems: Review of Recent Trends

Abstract: MIMO-OFDM is a key technology and a strong candidate for 5G telecommunication systems. In the literature, there is no convenient survey study that rounds up all the necessary points to be investigated concerning such systems. The current deeper review paper inspects and interprets the state of the art and addresses several research axes related to MIMO-OFDM systems. Two topics have received special attention: MIMO waveforms and MIMO-OFDM channel estimation. The existing MIMO hardware and software innovations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 140 publications
0
21
0
Order By: Relevance
“…The PDSCH throughput of a transmitting or receiving chain is presented with LTE System Toolbox functions. Channel noise is included in the simulation but later is demodulated by OFDM technique [17].…”
Section: Resultsmentioning
confidence: 99%
“…The PDSCH throughput of a transmitting or receiving chain is presented with LTE System Toolbox functions. Channel noise is included in the simulation but later is demodulated by OFDM technique [17].…”
Section: Resultsmentioning
confidence: 99%
“…MIMO-Aware Spectrum Access and Scheduling [18] and Global Path Planning Method for Mobile Robots Based on Teaching-Learning-Based Optimization [20] have proposed in Multi-hop Multi-channel Wireless Networks Zongsheng et al [19] presented a novel global path planning method for mobile robots for identification of shortest path between source to destination. Harkat, H.et al [21] reported a survey of recent works concerning channel estimation and the equalization process for MIMO-OFDM system. Khwandah, S.A [22] presented more about MIMO technology evolution and challenges in a simple introductory way and investigate potential system enhancements.…”
Section: Related Workmentioning
confidence: 99%
“…Implementing OFDM for 5G systems faces challenges like inter-carrier interference and high peak-to-average power ratios [12]. Additionally, IoT applications require waveforms with sub-millisecond latencies, further driving advancements in OFDM technology [13].…”
Section: Introductionmentioning
confidence: 99%